Քրդական գործոնի աշխարհաքաղաքական դերը - Հարությունյան, Ավագ («Զանգակ - 97»)
The geopolitical role of Kurdish factor in Near Eastem region is very imporlant. The Armenian-Kurdish relations have historical and political aspects. The Kurdish factor is very actual and vital for Russia, Turkey, Iran, Syria, USA and European Union. Around the Kurdish factor Armenia, Russia and Iran can cooperalc againsl USA.
Keywords: Պատմություն